Development of Professionally-Oriented Reading Skills of Future Veterinarians - Liudmyla Pikulytska (Educational Challenges)
The article deals with the development of future veterinarians’ professionally-oriented reading skills during foreign language learning. The article's aim is to highlight and analyze the main directions of the development of professionally-oriented foreign reading skills of future veterinarians as one of the effective methods of mastering foreign language competence. The objectives of the article are to study and characterize the theoretical foundations of professionally-oriented reading training; to define principles and criteria for the selection of professionally-oriented texts for future veterinarians; to introduce and substantiate the stage-by-stage work with the text of professional veterinary orientation. General theoretical research methods (analysis, synthesis, system-structural) have been used to reach the research purpose. The results are the following. The teacher’s work on developing reading skills is not only to teach the students to read but also to encourage them to use learned material in their future professional activities. Properly selected training material on professionally-oriented reading takes a leading role in the successful training of future veterinarians. The problem of the selection of training material for the formation of professional competence in reading was solved by taking into account the criteria of authenticity, informativeness, and accessibility of texts. In the process of selecting materials for training professionally-oriented reading at the faculty of veterinary medicine, it is appropriate to rely on the principles of professional orientation; scientificity; sustainability; unity of theory and practice. As an outcome of the research, we have concluded that the development of professionally-oriented reading skills helps to solve a number of tasks: it gives the motivation to learn a foreign language, allows students to deepen their knowledge of scientific authentic material, develops abilities to use foreign sources in future professional activities, improves skills of professional communication.